CONCEPTUALISATION OF ECONOMIC CRISIS IN DISCOURSE: FROM THE GREAT DEPRESSION TO THE GREAT RECESSION - Natalya Oliynyk; Iryna Shevchenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article considers conceptual representation of ECONOMIC CRISIS in the economic mass-media discourse of the two historical periods: 1929-1933 and 2007-2010 to reveal its synchronic and diachronic distinctions and dichotomies. More specifically, it is aimed to study linguistic means representing the concept in the 20th century and determine their diachronic variations. Applying cognitive linguistic instruments, such as component analysis and conceptual metaphor theory, it has been determined that conceptual content, structure and metaphorical representation of ECONOMIC CRISIS are subject to historical variations. Terminologically motivated name of the concept "economic crisis" provides historical stability of its content and structure formed by historical constants DECLINE, UNSTABLE SITUATION, TURNING POINT on the one hand, and affects its historical change: extension with new constituents - variables DISORDER, LANDMARK, ACCIDENT, on the other. Propositional schemas of the concept, mainly those of action and identification, form the cognitive structure of ECONOMIC CRISIS and vary diachronically in the degree of prominence. The dominant conceptual metaphors of ECONOMIC CRISIS of a target domain CRISIS is MOVEMENT DOWN and CRISIS is A STATE OF EMERGENCY are stable through history while their further division into clusters of metaphors varies both in the set of source domains and in their frequency in discourse.